Anaerobic sludge digestion elevates dissemination risks of bacterial antibiotic resistance in effluent supernatant. (15th July 2023) - Li, Xia; Chen, Guowei; Liu, Li; Wang, Gang
Abstract: Anaerobic digestion following a variety of pretreatments is a promising technique for the reduction of excess sludge in municipal wastewater treatment plants (MWWTPs), and eliminations of possible pathogens, viruses, protozoa, and other disease-causing organisms. Notwithstanding a rapidly increasing health concern of antibiotic resistant bacteria (ARB) in MWWTPs, dissemination risks of ARB in anaerobic digestion processes are still poorly understood, especially in the digested supernatant. Taking the representative ARB with respect to the common tetracycline-, sulfamethoxazole-, clindamycin- and ciprofloxacin resistance, we investigated the compositions of ARB in the sludge and supernatant, and quantified their variations along the entire anaerobic sludge digestion process following ultrasonication-, alkali-hydrolysis- and alkali-ultrasonication pretreatments, respectively. Results showed that the abundance of ARB was diminished by up to 90% from the sludge along anaerobic digestion coupling with the pretreatments. Surprisingly, pretreatments clearly boosted the abundance of specific ARB (e.g., 2.3 × 10 2  CFU/mL of tetracycline-resistant bacteria) in the supernatant that otherwise remained relatively low value of 0.6 × 10 2  CFU/mL from the direct digestion. Measurements of the soluble-, loosely-bound- and tightly-bound extracellular polymeric substances components revealed a gradually intensified destruction of the sludge aggregates along the entire anaerobic digestion processes, which could be likely responsible to the increase of the ARB abundance in the supernatant. Furthermore, analysis of the bacterial community components showed that the ARB populations were strongly correlated with the occurrence of Bacteroidetes, Patescibacteria, and Tenericutes. Interestingly, intensified conjugal transfer (0.015) of antibiotic resistance genes (ARGs) was observed upon returning of the digested supernatant to the biological treatment system. It implies the likelihood of ARGs spreading and subsequent ecological risks upon anaerobic digestion towards reducing excess sludge, and therefore requires further attentions for the excess sludge treatments especially of supernatant. Graphical abstract: Image 1 Highlights: Anaerobic sludge digestion elevates ARB abundance up to 90% in the supernatant. Sludge pretreatments intensify ARB abundance in the supernatant. Pretreatments stimulate conjugal transfer frequency of ARGs to 0.015 in supernatant. ARB spread correlates with Bacteroidetes, Patescibacteria, and Tenericutes.